Longman introductory course for the TOEFL test IBT - Phillips, Deborah 1952- (White Plains, N.Y Longman, 2007)
This course is designed to help intermediate students increase their scores in all sections of the TOEFL Test, including the Test of Written English. The course features skills and strategies for each section of the Test, abundant practice, two complete practice tests, and a teacher's manual
With Answer Key
1 2
Keywords: English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides; Test of English as a Foreign Language -- Study guides